2021
DOI: 10.3389/fmicb.2021.759170
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Citrulline and Glutamine Contribute to Reverse the Resistance of Salmonella to Apramycin

Abstract: Antibiotic resistance is an increasing concern for human and animal health worldwide. Recently, the concept of reverting bacterial resistance by changing the metabolic state of antibiotic-resistant bacteria has emerged. In this study, we investigated the reversal of Apramycin resistance in Salmonella. First, non-targeted metabonomics were used to identify key differential metabolites of drug-resistant bacteria. Then, the reversal effect of exogenous substances was verified in vivo and in vitro. Finally, the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…Increased central carbon metabolism, especially the TCA cycle, is the core of metabolome reprogramming. Our previous work confirmed that citrulline and glutamine enhanced the apramycin-mediated killing of Salmonella via the TCA cycle (Yong et al, 2021). In the current study, D-ribose significantly increased central carbon metabolism.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Increased central carbon metabolism, especially the TCA cycle, is the core of metabolome reprogramming. Our previous work confirmed that citrulline and glutamine enhanced the apramycin-mediated killing of Salmonella via the TCA cycle (Yong et al, 2021). In the current study, D-ribose significantly increased central carbon metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…Exogenous supplementation to reprogram the metabolome by repressed metabolites can alter the sensitivity of resistant strains ( Peng et al, 2015b ). Our previous study confirmed that citrulline and glutamine promoted apramycin-mediated killing ( Yong et al, 2021 ). The current study confirmed that exogenous D-ribose, which was suppressed in SCH-R, enhanced gentamicin-mediated killing in both SCH-R and SCH2021.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Metabolites-enabled killing efficacy by antibiotics is related to both antibiotic types and classes and bacterial species (Peng et al, 2015b;Zhao et al, 2021). Although glutamine potentiates antibiotic-mediated killing has been reported, only glutamine-enabled killing of E. coli by ampicillin, of Salmonella by apramycin, and of Mycobacterium persisters by rifampicin are carefully studied (Huang et al, 2018;Yong et al, 2021;Zhao et al, 2021). The present study identifies metabolites that potentiate gentamicin-mediated killing efficacy and determines glutamine-enabled killing of lab-evolved gentamicin-resistant E. coli and clinically isolated multidrug-resistant E. coli.…”
Section: Discussionmentioning
confidence: 99%